Arterial hypertension as a predictor of morpho- densitometric changes development in rats` solitary-vagal complex - Danukalo, M. V.; Melnikova, O. V. (Journal of Education, Health and Sport, 2019)
The components of the dorsal vagal complex: the nucleus of the solitary tract (NST) and the dorsal motor nucleus (DMN) are key structures in BP regulation. The maintenance of BP normal level depends on functional state of these structures. it is possible to estimate the neuron morpho-functional state not only with direct electrophysiological methods but also analyzing the nucleus size and nucleic acid (NA) concentration in it. Therefore, the aim of our work was to determine the features of morpho-densitometric indices in the nuclei of the NST and DMN neurons in AH of various origins in experimental animals and to give a comparative analysis of these data. Materials and methods: the study was carried out on 30 mature male rats: 10 control Wistar rats, 10 Wistar rats with modeled endocrine-salt AH (ESAH) and 10 spontaneously hypertensive rats (SHR) which are well-established model of human essential arterial hypertension (EAH). The histochemical method of staining with gallocyanine-chrome alum by Einarson was used for the evaluation of morpho-densitometric characteristics of the DMN and NTS neurons` nuclei: the nucleus area, the content and concentration of nucleic acids in the nucleus.Conclusions: The following conclusions can be made as a research result: 1. Morpho-densitometric changes occur in NTS and DMN in arterial hypertension, regardless of its pathogenesis. 2. The most distinct changes of the studied indices of neurons` nuclei were observed in DMN of the rats with EAH. Although only the neurons` nuclei area significantly changed in the NTS. The distribution of neurons` nuclei by their area in DMN and NTS in SHR rats showed a downward trend. 3. Significant decrease in all morpho-densitometric characteristics of the neurons` nuclei is observed in the DMN in the rats with an ESAH. The distribution of neurons` nuclei by their area showed a tendency to decrease. In the nuclei of NST neurons, only the content and concentration of NA were reliably low in comparison with control animals. The distribution curve of neurons by the area of their nuclei in ESAH rats is characterized by wider variability of size than in the control group.